Peningkatan Hasil Belajar dengan PBL Berbasis Power Point Pada Fonologi: Pelafalan Kata Anak - Wibowo, Henry Aji; Anwar, Khoirul (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This study uses mixed methods, a simultaneous integration of quantitative and qualitative techniques-through the use of PowerPoint presentations to provide a more complete and comprehensive picture of the problem under investigation and to improve students' comprehension of phonology (word pronunciation). The results of the study indicate that first-year SD Negeri 73 Gresik students' phonological knowledge may be improved by using PowerPoint. This was demonstrated by the average score rising from 59 on the pretest to 83 on the posttest. Individual grades also improved: 18 out of 20 pupils experienced an improvement in their grade. The study's findings are consistent with the idea that using PowerPoint to teach phonology increases students' phonological awareness. PowerPoint presentations may be used to spice up lectures, increase students' excitement for studying, and make the material easier to understand.